ROSAI DORFMAN DISEASE WITH EXTENSIVE BONY INVOLVEMENT- A DIAGNOSTIC DILEMMA - Maria Zahid Ahmed,; Mahmood, Madiha; Langhani, Jawaharlal; Zohair, Muhammad; Virk, Mahnoor; Mubarak, Muhammad; Akhtar, Fazal; Ahmed, Ejaz (Journal of Ayub Medical College Abbottabad, 2023)
Previously classified as Non Langerhan cell histiocytosis by Working Group of Histiocytic Society in 1987 Rosai Dorfman Destombes disease was first described by Destombes in 1965 and later in 1969 by Rosai and Dorfman as a rare histiocytic disorder with sinus histiocytosis and massive lymphadenopathy. They exist as both nodal and extranodal forms. Immunohistochemistry is an essential part of diagnosis as to differentiate between Langerhans cell histiocytosis and another malignant histiocytosis. Some overlap has also been reported with IgG4-related diseases. We hereby reflect upon a patient who presented to our facility with pyrexia of unknown origin, the challenges faced in order to reach a diagnosis and the management offered.